Um estudo sobre a trajetória socioeconômica de egressos da educação profissional e tecnológica do Instituto Federal do Paraná campus Assis Chateaubriand - Manini, Simone Moro (2023)
The offer expansion of professional education by the Federal Government occurred mainly through the creation of Federal Institutes. Their performance must be articulated to the territorial context, aiming at strengthening local productive, social, and cultural arrangements, highlighting socioeconomic development. The aim of this research was to analyze the contribution of Professional and Technological Education to socioeconomic changes in the graduates' lives from Federal Institute of Paraná Campus Assis Chateaubriand. This research was carried out with high-school students graduating between 2011 and 2018 in Electromechanics, Electrotechnics and Informatics technical courses, and with professors who were their coordinators in the same period. Two structured questionnaires were used for data collection. The results showed that the graduates of the Integrated courses sought professional education as a way of preparing for access to higher education. They managed to succeed in continuing their studies, since a high percentage attended or is attending some graduate course. For the graduates of the Subsequent courses, the main reason given by them to take the technical course was the opportunity to train or update their knowledge. Most of these graduates’ work in an area strongly related to the training obtained. Most students remained in the municipality or in the Western Paraná Mesoregion, highlighting the contribution of the Campus to the strengthening of local and regional human capital. The knowledge learned by the graduates helped them both in professional and academic performance. In addition, technical education allowed them to have knowledge and development of skills in several areas. During the studies, students had access to many activities that contributed to broaden their learning, but the lack of financial resources was identified as a limited factor for the development of these actions. The students recognized the quality of the education offered by IFPR Assis Chateaubriand through the evaluation of the courses and the Institution. Thus, it was concluded that the Professional and Technological Education offered by the IFPR Assis Chateaubriand provided positive contributions to the students.